Membangun Komitmen Kerja Melalui Faktor-Faktor Motivasi Di Lingkungan Pegawai Negeri Sipil - Nurmantyo, Eka (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2021)
The goal of maintaining employees is performance. Hopefully, through the performance of all organizational goals are achieved. This research is supposed to find out what factors enable employees to work well, especially those related to work commitment. For that, we need a research approach, namely quantitative. Thus clear information is obtained. In practice, test analysis uses path analysis. As for the unit of analysis are civil servants in the Banten province education office. The results showed that motivation was proven as a mediating variable for commitment. This means that many independent factors influence, but not directly, on work commitment.